Repeatable self-healing bendable concrete - Chan, Carissa Qing Xuan (Nanyang Technological University, 2021)
The self-healing behaviour of cementitious materials has attracted great attention as it mitigates damages inflicted on concrete structures. The repeatability of this self-healing behaviour is considered an important attribute since these concrete structures require self-repair for multiple damages in their service life. The ordinary Portland cement (OPC) based cementitious materials do not have good repeatability in their autogenous healing according to their previous studies. However, reactive magnesia cement (RMC) has shown great potential in their autogenous healing performance. Therefore, it is necessary to investigate the repeatability of autogenous healing in RMC-based cementitious materials. In this paper, a research was carried out to understand the repeatability of self-healing in RMC-based strain-hardening cementitious composites (SHCC). The dog-bone shaped RMC-based SHCC specimens were subjected to four damaging-healing cycles. They were loaded to 0.5% tensile strain before undergoing the autogenous healing process. The healing regime included submerging of the specimens into room temperature water for one day and drying the wet specimens at laboratory ambient environment for another day. A total of 10 such wetting and drying cycles were applied. The cracks generated during the tensile preloading were analysed before and after the healing process. The resonant frequency (RF) of the specimens was measured after each wetting and drying cycle. The same procedure was carried for some OPC-based SHCC specimens to allow comparison of the two. The results showed that the RMC-based SHCC specimens demonstrated much better repeatability in their self-healing behaviour when compared to that of the OPC-based SHCC specimens. The normalised RF of the RMC-based SHCC specimens were able to recover and even reach more than 100% after several damaging-healing cycles. On the other hand, the normalised RF of the OPC-based SHCC specimens were only able to reach around or even less than 80% after their damaging-healing cycles. It was also observed that the cracks of the RMC-based SHCC specimens generated during the four damaging-healing cycles were distributed evenly along the specimens’ lengths. However, the cracks of the OPC-based SHCC specimens generated during the second and third damaging-healing cycles were mostly at the locations of the cracks from the first damaging-healing cycle. With the information put together, it can be interpreted that the self-healing in the RMC-based SHCC specimens were much more robust and repeatable.